INFORMATION SYSTEM DESIGN FOR MICRO CREDIT BANKS - Linda Wahyu Widianti (Majalah SIKOMTEK, 2004)
Developments in the banking system nder its wings for small businesses (market traders),which are many and are the backbone of the people on the Indonesian economy. To help thesmall entrepreneurs who are usually very shy in touch with the bank. Products of this microservice within its implementation constitute a computer-based information systems andmanagement processes utilizing information technology as a tool for data processing.Information system used for calculation of return on a loan and is available at this microservice are semi automatic because many feel That matter deficiencies. Disadvantagesinclude the ineffectiveness of the time used in making the loan payment calculation reports ofcustomers, it is disturbing performance in the billing clerk.Micro-services information system design of the proposed implementation will be realizedbyusing a computer. This system can provide advantages such as speed up the preparation ofreports and data storage more reliable, so it can provide accurate and reliable information thatwill ultimately produce an effective performance and efficient performance in supporting thedecision making process for its users